In vitro assessment of probiotic properties of lactic acid bacteria isolated from camel milk: enhancing sustainable foods - Nawaz, Zeeshan; Zahoor, Muhammad Kashif; Shafique, Muhammad; Athar, Rasham; Yasmin, Aysha; Zahoor, Muhammad Asif (Frontiers in Sustainable Food Systems, 2024)
Probiotic properties of isolated lactic acid bacteria (LAB) from sustainable foods including camel milk are the potential research domains. For this purpose, camel milk samples (n=20), from four different herds of Camelus dromedarius, were processed for the identification of LAB strains based on biochemical profiles followed by amplification and sequence analysis of the 16S rRNA gene. The probiotic characteristics i.e., acids and bile salts tolerance, antimicrobial susceptibility profiles, hemolytic and antimicrobial activities, auto-aggregation assay, and adhesion to HT-29 epithelial cells were determined. 13 out of 20 milk samples were initially found positive for the growth of probiotics or LAB which were further confirmed as Lacticaseibacillus casei (5) and Pediococcus pentosaceus (3). The probiotics/ LAB strains showed maximum survival (%) = 92.06 ± 1.82 and 81.35 ± 3.64 against acids and bile salts, respectively. The LAB strains were found sensitive to amoxicillin, ceftazidime, imipenem, linezolid, ofloxacin, tetracycline, tobramycin, and vancomycin. None of the LAB strains showed hemolytic activity. L. casei-04 strain showed a maximum zone of inhibition (15.33 ± 0.58) against multidrug-resistant E. coli AZ1 strain whereas, L. casei-05 showed a maximum zone of inhibition (16.33 ± 1.15) against methicillin-resistant S. aureus Saba-1 strain. L. casei-03 showed maximum percentage auto-aggregation (28.65 ± 1.96) at 4 hours while L. casei-01 showed (41.10 ± 3.03) at 24 hours of incubation. Maximum adhesion was shown by P. pentosaceus-01 (11.14%) followed by L. casei-02 (9.73%). Altogether, the current findings suggested that camel milk has significant potential of providing probiotics/ LAB strains into human food chain and enabling camel milk as potential sustainable food.